Electrochemical Reduction of TiO2/Al2O3/C to Ti3AlC2 and Its Derived Two-Dimensional (2D) Carbides. Issue 3 (8th February 2018) - Li, Shangshu; Zou, Xingli; Hu, Yong; Lu, Xionggang; Xiong, Xiaolu; Xu, Qian; Cheng, Hongwei; Zhou, Zhongfu
Abstract : Ti3 AlC2 has been directly synthesized from TiO2 /Al2 O3 /C mixture precursors (3TiO2 /0.5Al2 O3 /1.5C and 2TiO2 /0.5Al2 O3 /C) by a molten salt electrolysis process at 900°C and 3.2 V in molten CaCl2 . The influence of initial carbon content on the electrosynthesized products has been investigated. The result shows that the main phase of the electrosynthesized products changes from Ti3 AlC to Ti2 AlC and then to Ti3 AlC2 with the increasing carbon content, and the electrosynthesized Ti3 AlC2 is carbon deficient. The morphology observation shows that the electrosynthesized Ti3 AlC2 particles possess smooth surfaces and dense flake-like microstructure. The reaction mechanism of the electroreduction of TiO2 /Al2 O3 /C mixture precursor has been discussed based on the time- and position-dependent phase constitution analysis. In addition, two-dimensional (2D) Ti3 AlC2 -derived carbides, i.e., Ti3 C2 T x and TiC x have been successfully prepared from the electrosynthesized Ti3 AlC2 by a chemical etching process and an electrochemical etching process, respectively. Both derived carbides exhibit the similar layered structure, in which single layer carbides are composed of plentiful nanometer carbides. It is suggested that the molten salt electrolysis process has a great potential to be used for the facile synthesis of M n +1 AX n phases (such as Ti3 AlC2 ) from their oxides precursors, and the synthesized M n +1 AX n phases can be further converted into 2D carbides.